New Family Relationships: between Bio-genetic and Kinship Rarefaction Scenarios - Simonetta Grilli; Rosa Parisi (Antropologia)
Since the ‘90s, there has been a renewal of interest on kinship studies produced by emerging topics within research into gender, personhood and particularly, the construction of kin relationships through Assisted Reproductive Technologies. The deconstruction of kinship as “a natural fact” has definitely questioned and challenged the genealogical dimension of kinship, which was traditionally based on the link between heterosexuality and procreation. The first part of this paper briefly reconstructs the new theories toward Euro-American kinship perceptions in anthropology. The focus is on the changes resulting from new assisted reproduction techniques, low fertility in relation to changes in genealogical space; and finally, issues relating to biopolitics. In the second part, starting from the ethnographic work that proponents have been conducting for years on homo-parental (same sex) families in Italy, the paper explores the way in which “new forms of family” are currently creating new textures of social cohesion and “relatedness”. The reflections of this paper focus on one hand, the different forms of procreative constructions and parenthood/intentional parenthood, and on the other, the production of “multiple genealogies”, new forms of relatedness and a new lexicon of relationships.